Persistent hyperglycemia in a neonate: Is it a complication of therapeutic hypothermia? - MEMİŞOĞLU, ASLI; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA; DEMİRCİOĞLU, SERAP (TURKISH J PEDIATRICS, 2017)
The aim of this report is to present a newborn with persistent hyperglycemia requiring insulin therapy as a possible complication of therapeutic hypothermia. A term appropriate for gestational age (AGA) female infant, was born by emergency cesarean section due to abruption of placenta and was resuscitated and intubated in the delivery room. Whole body cooling was initiated according to standard cooling criteria. The patient's blood glucose increased up to 250 mg/dl on a glucose perfusion rate of 6 mg/kg/min after the second day of cooling. Insulin therapy was started due to persistent hyperglycemia and continued for 17 days. As it has been reported in adults after therapeutic cooling, persistent hyperglycemia attributed to hypothermia can also complicate therapeutic hypothermia in neonates.
Keywords: asphyxia; hyperglycemia; hypothermia; newborn; INSULIN-SECRETION; NEWBORN-INFANTS; ENCEPHALOPATHY; GLUCOSE; RAT